Massive MIMO systems for underwater acoustic communication - Lawal, B. (Institute of Electrical and Electronics Engineers Inc., 2017)
Underwater wireless communication systems (UWS) or underwater wireless sensor networks (UWSN) consist of different devices or networks of interconnected devices such as underwater acoustic sensors, autonomous underwater or unmanned underwater vehicles (AUV or UUV) and Remotely Operated Vehicle (ROV). These devices are equipped with sensing, processing, and communication capabilities deployed underwater for several specific applications. Most of these applications are multimedia coastal and tactical surveillance, picture and video acquisition and classification, offshore/oil exploration, pollution monitoring and reporting, military defence, oceanographic data collection, and search and rescue operations. These applications entail delay-sensitive and high data traffic as well as loss-sensitive traffic data. However, the underwater environment has unique characteristics and constraints such as high delay, increased error rate, low bandwidth, impaired channel due to multi-path and fading problems, high attenuation and high power consumption. To guarantee QoS of the high traffic data generated due to these applications; massive multi-input multi-output (Massive MIMO) system is considered as the best promising solution to enhance underwater communication for improved throughput/capacity, spectral and energy efficiency. © 2016 IEEE.